THE SOCIO-PHILOSOPHICAL INTERPRETATION OF DEVELOPING STUDENTS’ CREATIVE THINKING IN THE NEW UZBEKISTAN - Sayfutdinovna, Abdullayeva Barno (PT. Antis International Publisher, 2025)
Objective: This article provides an in-depth analysis of the socio-philosophical interpretation of the formation of students' creative thinking in the conditions of New Uzbekistan, emphasizing its importance during the post-independence period marked by large-scale reforms, modernization of the education system, development of human capital, and the implementation of the principle of